Modified extragradient algorithms for solving monotone variational inequalities and fixed point problems. (1st September 2020) - Zhao, Xiaopeng; Yao, Yonghong
Abstract : In this paper, we investigate the monotone variational inequalities and fixed point problems in Hilbert spaces. Two modified extragradient algorithms are presented for finding a common element of the set of fixed points of a pseudocontractive operator and the set of solutions of the variational inequality problem. Weak and strong convergence of the suggested algorithms are proved.